Analisis Potensi Pasar Internasional Sambal Kemasan Dede Satoe Surabaya dengan Pendekatan Bisnis Model Kanvas - Yunanda, Gabela Astrilia (BALANCE: Economic, Business, Management and Accounting Journal, 2023)
ABSTRACT   With dynamic competition conditions, a business needs to re-analyze the company's condition internally and the existing or new market (potential market). In a business context, reviewing the business model to analyze the company's internal conditions must be done periodically. This is a consequence of dynamic industrial conditions shifting market conditions and as a reference and anticipatory and adaptive steps in running a business. This research analyzes the company's internal conditions and identifies existing markets or new markets (potential markets) using a qualitative case study method through a canvas business model approach so that companies focus more on specific consumer targets. The results of this research are in the form of formulating a new Canvas Business Model to reach international markets, mapping operational activities that UKM Dede Satoe Surabaya can develop to reach new market targets, mapping potential countries that can become new market segmentation reach, and adding 8 (eight) ) recommended strategies for market penetration that can be a reference for UKM owners Dede Satoe Surabaya